Mauritius : A Competitiveness Assessment - Minoiu, Camelia (IMF Working Papers; Working Paper ;, 2008)
We assess the competitiveness of Mauritius in recent years using two approaches. First, we estimate the difference between the equilibrium and the actual real exchange rate using four methods: the macroeconomic balance approach, the single-equation fundamentals approach, the capital-enhanced approach, and the external sustainability approach. The methods consistently suggest that at the end of 2007 the exchange rate was aligned with its equilibrium value. Second, we undertake a comparative analysis of structural competitiveness indicators and find that Mauritius often fares better on business climate than other small island economies and high-growth Asian economies. Nevertheless, there are areas for improvement.